2015
DOI: 10.2147/tcrm.s92121
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of efficacy of the intermittent pneumatic compression with a high- and low-pressure application in reducing the lower limbs phlebolymphedema

Abstract: IntroductionThe primary lymphedema and chronic venous insufficiency present an important medical problem, and effective physical therapeutic methods to treat this problem are still at the search phase. The aim of this study was to compare the efficacy of intermittent pneumatic compression (IPC) of a high- or low-pressure level in the treatment of primary phlebolymphedema of the lower limbs.MethodsThe study included 81 patients with chronic venous insufficiency and primary lymphedema of the lower limbs. Group A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…In patients with chronic venous edema, a dose-dependent relationship was reported between high pressure and leg edema [24] . However, when comparing groups receiving a high pressure intervention (120 mm Hg) and a low pressure intervention (60 mm Hg) as well as a control group without IPC among patients with chronic venous insufficiency and primary lymphedema, swelling was reduced most significantly in the high pressure group [25] . Furthermore, applying IPC at 100 to 120 mm Hg for 3 years in patients with stage II–III lymphedema in the lower limb did not lead to notable complications [26] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In patients with chronic venous edema, a dose-dependent relationship was reported between high pressure and leg edema [24] . However, when comparing groups receiving a high pressure intervention (120 mm Hg) and a low pressure intervention (60 mm Hg) as well as a control group without IPC among patients with chronic venous insufficiency and primary lymphedema, swelling was reduced most significantly in the high pressure group [25] . Furthermore, applying IPC at 100 to 120 mm Hg for 3 years in patients with stage II–III lymphedema in the lower limb did not lead to notable complications [26] .…”
Section: Discussionmentioning
confidence: 99%
“…[ 24 ] However, when comparing groups receiving a high pressure intervention (120 mm Hg) and a low pressure intervention (60 mm Hg) as well as a control group without IPC among patients with chronic venous insufficiency and primary lymphedema, swelling was reduced most significantly in the high pressure group. [ 25 ] Furthermore, applying IPC at 100 to 120 mm Hg for 3 years in patients with stage II–III lymphedema in the lower limb did not lead to notable complications. [ 26 ] In their 2013 study, Zaleska et al [ 27 ] reported that a high pressure of about 120 mm Hg and at least 50 seconds of compression are required to produce efficient tissue fluid pressure and generate proximal flow.…”
Section: Discussionmentioning
confidence: 99%
“…25 The use of LED-specific treatment in these patients has been shown to be beneficial, with prior studies showing improvement in both patient symptoms and economic burden. 9,26 However, the delay in initiating LED-specific therapy after venous intervention seen in this study suggests that there may be under-recognition of coexisting lymphedema in CVI patients, and further studies are warranted to determine if there is underutilization of LED-specific treatment.…”
Section: Discussionmentioning
confidence: 90%
“…Multiple-chamber garments typically provide sequential compression in an ascending pattern up the limb. Pumps vary in timing cycles and amount of pressure produced, ranging from low-pressure, slow-inflation to high-pressure, rapid-inflation devices [6].…”
Section: Introductionmentioning
confidence: 99%
“…Research regarding the efficacy of IPC is limited. Whilst early studies suggested that MLD and IPC are equally as effective in reducing upper limb oedema [7], studies examining sequential IPC as a treatment for lower limb lymphoedema [1, 6, 8, 9] demonstrated a lack of consensus with regard to treatment parameters. Historically, IPC pumps have used sequential cycles to provide a peristaltic massaging effect along the limb towards its root.…”
Section: Introductionmentioning
confidence: 99%